2001
DOI: 10.1046/j.1365-3083.2001.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Characterization of Antigens Encoded by the RD1 Region of the Mycobacterium tuberculosis Genome

Abstract: Development of immunoassays specific for the diagnosis of tuberculosis requires antigens unique to Mycobacterium tuberculosis. In a search for such antigens we tested six proteins encoded by RD1, a region present in M. tuberculosis and virulent M. bovis genomes but missing from the DNA of all substrains of M. bovis Bacillus Calmette-Guerin (BCG). The six proteins (Rv3871, Rv3872, Rv3873, MTSA-10, ESAT-6 and Rv3878) were purified to near-homogeneity from recombinant Escherichia coli. When tested for the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
2
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 26 publications
(44 reference statements)
0
59
2
4
Order By: Relevance
“…The high specificity of the Rv3879c peptides (97.4%), together with the fact that they are recognized in the IFN-␥ ELISPOT assay by almost half of TB patients, identifies this molecule as a potentially useful T-cell antigen for inclusion in novel T-cellbased diagnostic tests of M. tuberculosis infection. Antibody responses to Rv3873 and Rv3878 have previously been studied in humans (14). Of 75 TB patients, none (0%) had antibodies to Rv3873 and only 5 (6.7%) had detectable antibody responses to Rv3878 (14), considerably lower than the rates of response to these antigens of our series of 49 culture-confirmed TB patients in IFN-␥ ELISPOT assays.…”
Section: Vol 72 2004 T-cell Responses To Novel M Tuberculosis Genementioning
confidence: 58%
See 1 more Smart Citation
“…The high specificity of the Rv3879c peptides (97.4%), together with the fact that they are recognized in the IFN-␥ ELISPOT assay by almost half of TB patients, identifies this molecule as a potentially useful T-cell antigen for inclusion in novel T-cellbased diagnostic tests of M. tuberculosis infection. Antibody responses to Rv3873 and Rv3878 have previously been studied in humans (14). Of 75 TB patients, none (0%) had antibodies to Rv3873 and only 5 (6.7%) had detectable antibody responses to Rv3878 (14), considerably lower than the rates of response to these antigens of our series of 49 culture-confirmed TB patients in IFN-␥ ELISPOT assays.…”
Section: Vol 72 2004 T-cell Responses To Novel M Tuberculosis Genementioning
confidence: 58%
“…Antibody responses to Rv3873 and Rv3878 have previously been studied in humans (14). Of 75 TB patients, none (0%) had antibodies to Rv3873 and only 5 (6.7%) had detectable antibody responses to Rv3878 (14), considerably lower than the rates of response to these antigens of our series of 49 culture-confirmed TB patients in IFN-␥ ELISPOT assays. Thus, the potential of these two RD1-encoded gene products to contribute to an improved diagnostic test for TB could only be recognized by evaluation of T-cell responses in TB patients.…”
Section: Vol 72 2004 T-cell Responses To Novel M Tuberculosis Genementioning
confidence: 58%
“…In mice it has been shown that the ESAT-6 1-15 epitope was recognized by as much as 25-35% of the total mycobacteria-reactive T cell repertoire recruited to the site of infection in the first phase of a recall response in C57BL/6J mice (9). The immunodominance of this epitope may be a consequence of the high expression of ESAT-6 during infection (32), as well as easy proteolytic access to the protruding part of the ESAT-6 molecule containing this epitope (33). However, it is known from viral studies that epitope dominance cannot only be explained in terms of peptide loading and affinity for MHC (34), and there are data to suggest that T cells responding to one Ag can actively interfere with T cells responding to another (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…2). No IFN-␥ release was found in response to the control peptide (ESAT-6 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ). In addition to the immunodominant P1 (ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] ) epitope, the analysis of peptides covering the full sequence of ESAT-6 revealed two additional subdominant epitopes to which T cells are not primed during the natural infection.…”
Section: Identification Of Subdominant Epitopes In Esat-6mentioning
confidence: 99%
“…PBS is a common biological buffer because it is isotonic (with similar osmolarity to the body) and non-toxic to cells. 202 Intra-dermal injections of PBS alone have been used as controls in studies 203,204 with reported histology of moderate dermal oedema and blood vessel dilation without inflammation in human skin. 205 Similarly previous experiments involving human skin demonstrated redness and swelling at 10 and 30 minutes associated with needle trauma, followed by mild or no inflammatory reaction 48 hours after intra-dermal saline injections.…”
Section: Limitations Of Experimental Protocols In the Main Studymentioning
confidence: 99%